What behaviors are disapproved? Experimental evidence from five dictator games - Raúl López-Pérez; Marc Vorsatz (Games, 2012)
The literature on social norms has often stressed that social disapproval is crucial to foster compliance with norms and promote fair and cooperative behavior. With this in mind, we explore the disapproval of allocation decisions using experimental data from five dictator games with a feedback stage. Our data suggests that subjects are heterogeneous in their disapproval patterns, distinguishing two main groups: (1) Subjects who only disapprove choices that harm them, and (2) subjects who disapprove socially inefficient choices.
Keywords: 330; approval; disapproval; dictator game; experiment; social norms